PEMASARAN BERAS (TINJAUAN STRUKTUR PERILAKU DAN PENAMPILAN PASAR) DI KABUPATEN KUBU KABUPATEN ROKANHILIR - Novia Dewi; Jum’atri Yusri; Muhammad Yamin Saputra (Indonesian Journal of Agricultural Economics, 2020)
This study aimed to analyzed the rice marketing used behavioral structure approach and market appearance in Kubu Rokan Hilir. The location of this study was determined purposive at Teluk Piyai and Teluk Piyai Pesisir. The method of this study used survey method. The respondent of this study were rice farmers and marketing agencies that involved. The result of this study concluded there were two marketing structures in this study; the first, the farmer sell rice to rice collector then it sell to wholesaler then it sell to rice milling in north Sumatera. The second, the farmer sell rice to rice milling in Kubu then it sell to resellers in Kubu. The market structure that occurs is oligopsoni market, small buyer, value of market share, rasio concentration, and Herfindhal index were not too different from every seller. Total market margin at Teluk Piyai is Rp. 1.057/kg with details of marketing cost is Rp. 501/kg and the profit is Rp. 557/kg, and total margin of rice milling is Rp. 2.000/kg with details of marketing cost is Rp. 351/kg and the profit is Rp. 1.649/kg. Total market margin at Teluk Piyai Pesisir is Rp. 1.100/kg with details of market cost is Rp. 505/kg and the marketing agencies profit is Rp. 595/kg, and total margin of rice milling is Rp. 2.000/kg with details of marketing cost is Rp. 361/kg and the profit is Rp. 1.639/kg.